Analisis Anggaran Belanja Daerah pada Dinas Bina Marga dan Sumber Daya Air Kota Bekasi Tahun 2019-2022 - Saffanah Rizki P; Mas Rasmini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the regional expenditure budget at the Department of Highways and Water Resources of Bekasi City in 2019-2022. The research object used is regional expenditure The research method used is descriptive with a quantitative approach. Data collection techniques used include observation, interviews, and literature studies. The Budget Realization Report (LRA) at the Department of Highways and Water Resources of Bekasi City in 2019-2022 is used as the population, and budget items and expenditure realization are used as samples. Descriptive statistics are used as the data analysis technique with the theory of regional expenditure analysis (Mahmudi, 2019). The results obtained regarding the analysis of regional spending at the Department of Highways and Water Resources of Bekasi City in 2019-2022 are spending variance has an average of 12.57% or categorized as preferred difference ((favourable variance), spending growth has an average of 22.61%, the harmony of operational spending to total spending has an average of 29.88% or categorized as less harmonious, the harmony of capital spending to total spending has an average of 70.11% or categorized as harmonious, and spending efficiency has an average of 87.43% or categorized as fairly efficient. From the description above, it can be concluded that the Department of Highways and Water Resources of Bekasi City for the years 2019-2022 was able to absorb budget expenditures according to its needs each year. This can be seen from its prudent use of the budget without exceeding the set budget, wise spending despite fluctuations in spending growth, prioritizing capital spending over operational spending, and efficiently managing the budget to achieve its goals.